Expression of Survivin in Basal-Like and Triple Negative Breast Carcinoma and Associations with Clinicopathological Parameters - A., Madatang; S.N., Mohd Nafi; H., Jaafar; W.F., Wan Abdul Rahman (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Triple negative breast carcinoma (TNBC) molecular subtype and its variant; basal-like triple negative (BLTN) carcinoma is an established poor prognostic indicator. The aim of this study is to analyse the survivin expression in TNBC and BLTN, and relating the results with clinicopathological parameters. MATERIALS AND METHODS: We conducted a cross sectional study using 94 archived formalin-fixed paraffin embedded tissue blocks of invasive breast carcinoma, no special type (NST). Estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth receptor 2 (HER2) were used as surrogate markers to classify the cases into molecular subtypes. Samples with triple negative phenotype (ER, PR and HER2 negative) were stained with CK 5/6 to identify the BLTN subtype. All the samples were also immunostained for survivin. RESULT: Out of 94 cases, 41.5% (39 cases) were TNBC. Among the TNBC cases, only 41.0% (16 cases) were BLTN subtype when they found to be positive for CK 5/6. Among 94 cases of invasive breast carcinoma, 28.7% (27 cases) were survivin positive with (53.8%) 21 cases were TNBC and (11%) 6 cases were non-TNBC (p< 0.001). Among 16 cases of BLTN subtype, only 8 cases were survivin positive (p = 0.752). Survivin expression was also statistically significant with tubule formation (p=0.029), nuclear pleomorphism (p=0.008), tumour grade (p=0.010), ER status (p< 0.001) and PR status (p=0.001). CONCLUSION: Survivin expression was statistically significant in invasive breast carcinoma. Even though the expression was significantly high in TNBC, it is not related to whether it is a basal-like or non-basal-like variant.